A novel anchorage technique for transnasal traction in rigid external maxillary distraction - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2013)
We describe an effective technique for anchorage of transnasal traction in the management of maxillary rotation during external distraction. (C) 2012 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: External distraction; Maxilla; Counter clock-wise rotation; Miniplate; LE-FORT-III; SYNDROMIC CRANIOSYNOSTOSIS; MIDFACE DISTRACTION; SKELETAL ANCHORAGE; OSTEOGENESIS; SYSTEM